1998
DOI: 10.1038/nm0198-078
|View full text |Cite
|
Sign up to set email alerts
|

TNF is a potent anti-inflammatory cytokine in autoimmune-mediated demyelination

Abstract: Multiple sclerosis (MS) is an inflammatory disease of the central nervous system (CNS) characterized by localized areas of demyelination. Although the etiology and pathogenesis of MS remain largely unknown, it is generally assumed that immune responses to myelin antigens contribute to the disease process. The exact sequence of events, as well as the molecular mediators that lead to myelin destruction, is yet to be defined. As a potent mediator of inflammation, the cytopathic cytokine, tumor necrosis factor (TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
320
1
5

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 522 publications
(333 citation statements)
references
References 24 publications
7
320
1
5
Order By: Relevance
“…The initial characterization of TNF À/À mice not only confirmed the potent proinflammatory activities of TNF but, unexpectedly, also provided compelling evidence for an antiinflammatory role of this cytokine [10]. The complexity of TNFmediated pro-, and anti-inflammatory effects in the induction of deleterious autoimmune responses has been demonstrated in a mouse model of multiple sclerosis: while TNF was found to be essential in promoting acute EAE in susceptible mouse strains, it subsequently limited the expansion of myelin oligodendrocyte glycoprotein-reactive T cells, and thus, the chronic phase of the disease.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The initial characterization of TNF À/À mice not only confirmed the potent proinflammatory activities of TNF but, unexpectedly, also provided compelling evidence for an antiinflammatory role of this cytokine [10]. The complexity of TNFmediated pro-, and anti-inflammatory effects in the induction of deleterious autoimmune responses has been demonstrated in a mouse model of multiple sclerosis: while TNF was found to be essential in promoting acute EAE in susceptible mouse strains, it subsequently limited the expansion of myelin oligodendrocyte glycoprotein-reactive T cells, and thus, the chronic phase of the disease.…”
Section: Discussionmentioning
confidence: 81%
“…For example, Liu et al observed exacerbation of demyelation and inflammation in an EAE model in the absence of TNF [10]. In type I diabetes in the NOD mouse, disease-promoting, as well as disease-attenuating effects by TNF have been observed depending on the time point of TNF administration [11], and in acute airway response to endotoxin, T-cell-derived TNF down-regulated the inflammation [12].…”
Section: Introductionmentioning
confidence: 99%
“…The present data may help to explain some apparently paradoxical effects of TNF-a and TNFRI during the development of chronic immune pathologies that involve T cells in mice. Early studies documented disease-promoting effects of TNF-a [30][31][32][33] and TNFRI 22,34 during disease initiation in experimental autoimmune encephalomyelitis, a model for multiple sclerosis and collagen-induced arthritis that were attributed to TNF/TNFRI-dependent control of leukocyte trafficking at the target organ. 30,35 Indeed, TNF-a blocking reagents ameliorate clinical symptoms and inflammation in patients with rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-a administration or expression from transgenes at T cell target sites protected mice in models of lupus, 37 autoimmune diabetes, 38 arthritis 39 and experimental autoimmune encephalomyelitis. 31 In experimental autoimmune encephalomyelitis, TNFRI KO mice also developed enhanced Ag-dependent T-cell proliferation and central nervous system inflammation 22 and TNF-a KO mice showed abnormally prolonged myelin-specific T-cell responses. 40 More recently, TNF was found to negatively regulate IFN-g and IL-17 production by T cells in collagen-induced arthritis, through inhibition of IL-12/IL-23 p40 expression and thereby probably Ag-presenting cell function.…”
Section: Discussionmentioning
confidence: 99%
“…TNF-␣ is produced by activated T cells (mostly Th1) and macrophages, and its elevated expression at the site of inflammation occurs during the critical phase of disease, 11 at the time when the 'secondary influx' of leukocytes is apparent. 3 Except for a single recent study carried out in genetically modified animals, 36 all investigators agree that TNF-␣ contributes to the pro-inflammatory process in EAE, and probably MS. 25,[37][38][39][40][41][42][43][44][45][46][47][48][49][50][51] Thus, inhibition of TNF-␣ activity by either neutralizing antibodies or soluble TNF receptor therapy, effectively prevents, or even reverses EAE. 25,42,45,[47][48][49][50][51] Overexpression of TNF-␣ in the CNS aggravated the dis-ease, 46 whereas genetically impaired expression of this gene inhibited the development and progression of disease.…”
Section: Introductionmentioning
confidence: 99%